Exploring Creative Business Ideas and Business Opportunities for Bina Amanah Cordova Entrepreneurship School Students - Aseanty, Deasy; Rahayu, Fatik; Lutfi, Muhamad Yudhi; Wijaya, Aji Kusuma (Jurnal Pengabdian Masyarakat Bestari, 2024)
Business success depends on the success of creating and realizing creative ideas in executing them. Basically, everyone is born with natural talents. Realizing your abilities and potential, and managing your talents effectively, is a good start if you want to become a successful entrepreneur. To move a business towards change and innovation, creativity is needed which produces brilliant ideas. Innovation in business development can emerge from reliance on internal creativity. Innovation and creativity are two concepts that are closely related and cannot possibly appear in humans in an instant. Educating and preparing students to be more creative and creative is the main thing. If they choose to become entrepreneurs, they must also strive to foster greater creativity and innovation so that their company can develop and grow.